Discussion on the Rehabilitation of Stroke Hemiplegia Based on Interdisciplinary Combination of Medicine and Engineering. (17th March 2021) - Sun, Xiaowei; Xu, Ke; Shi, Yuqing; Li, Hongtao; Li, Ruobing; Yang, Siyu; Jin, Hong; Feng, Chuwen; Li, Baitao; Xing, Chunyue; Qu, Yuanyuan; Wang, Qingyong; et al.
Abstract : Interdisciplinary combinations of medicine and engineering are part of the strategic plan of many universities aiming to be world-class institutions. One area in which these interactions have been prominent is rehabilitation of stroke hemiplegia. This article reviews advances in the last five years of stroke hemiplegia rehabilitation via interdisciplinary combination of medicine and engineering. Examples of these technologies include VR, RT, mHealth, BCI, tDCS, rTMS, and TCM rehabilitation. In this article, we will summarize the latest research in these areas and discuss the advantages and disadvantages of each to examine the frontiers of interdisciplinary medicine and engineering advances.